Efficacy of Kegan Liyan oral liquid vs. Lianhuaqingwen capsules for patients with mild COVID-19: a double-blinded, randomized, controlled, non-inferiority trial - Li, Yuewei; Chi, Yihe; Zhu, Mengting; Fan, Feiting; Deng, Zhongyang; Xiao, Jingmin; Jin, Shaohan; Lin, Luoqi; Chen, Xiaochun; Xu, Ruhong; Fan, Long; Yu, Xuhua; et al. (Frontiers in Medicine, 2025)
BackgroundTraditional Chinese medicine has been used for Coronavirus disease 2019 (COVID-19) as a therapeutic option. Lianhuaqingwen capsules (LHQW) are well-recognized for their efficacy, while Kegan Liyan oral liquid (KGLY), widely used for influenza treatment, has emerged as a promising candidate for COVID-19 therapy. This trial aims to assess whether KGLY is non-inferior to LHQW in treating mild COVID-19.MethodsA total of 127 participants (63 in KGLY group and 64 in LHQW group) were randomly allocated to receive either KGLY therapy or LHQW therapy in a 1:1 ratio. The treatment was given for 7 days, and the follow-up period was 3 days.Outcome measuresThe primary outcome was symptom remission at day 10. Secondary outcomes included symptom recovery, time to symptom remission, recovery rates and time to recovery of selected symptoms, change in visual analog scale score for selected symptoms, area under the curve of the visual analog scale score for sore throat, negative conversion of the SARS-CoV-2 infection, having a positive test result after negative conversion, and incidence of pneumonia.ResultsFull analysis set analysis showed that the symptom remission rate at day 10 was 60.7% with KGLY and 58.3% in LHQW (difference + 2.3 p.p., lower limit of 95% confidence interval − 14.8 p.p.), indicating non-inferiority. There were no significant differences between the groups for any secondary outcome. The occurrence of adverse events did not differ between the groups and no severe adverse events were documented in either group.ConclusionBased on the study results, this trial proved that KGLY was non-inferior to LHQW for mild COVID-19, providing a promising option for COVID-19 treatment.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=166372, Identifier, [ChiCTR2200059105].